2022
DOI: 10.3390/ma15197006
|View full text |Cite
|
Sign up to set email alerts
|

A Water-Stable Zn-MOF Used as Multiresponsive Luminescent Probe for Sensing Fe3+/Cu2+, Trinitrophenol and Colchicine in Aqueous Medium

Abstract: A water-stable Zn-MOF was constructed based on H2PBA and 1, 10-phenanthroline under solvothermal conditions. The compound exhibited a 3D (2,3,8)-connected (43)2(46.66.815.12)(8) topology framework. The crystal structure and phase purity of the compound was verified by single crystal X-ray diffraction. Subsequently, some studies on the morphology, structure, and luminescent properties were carried out. The results showed that this compound could be used as a versatile chemosensor for Fe3+/Cu2+, trinitrophenol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…At present, fluorescent probes have been widely investigated for detecting Cu 2+ [12,13]. Among them, metal-organic frameworks (MOFs) have aroused considerable interest owing to their flexible and adjustable structure, porosity, and large specific surface area, which is beneficial for concentrating trace amounts and enhancing the contact area between the probe and the analyte [14][15][16][17]. Wang et al designed the fluorescent probe AuNCs/ZIF-8, which exhibited fluorescence turn-off responses to Cu 2+ in the concentration range of 2-15 µM with a detection limit of 0.9 µM [18].…”
Section: Introductionmentioning
confidence: 99%
“…At present, fluorescent probes have been widely investigated for detecting Cu 2+ [12,13]. Among them, metal-organic frameworks (MOFs) have aroused considerable interest owing to their flexible and adjustable structure, porosity, and large specific surface area, which is beneficial for concentrating trace amounts and enhancing the contact area between the probe and the analyte [14][15][16][17]. Wang et al designed the fluorescent probe AuNCs/ZIF-8, which exhibited fluorescence turn-off responses to Cu 2+ in the concentration range of 2-15 µM with a detection limit of 0.9 µM [18].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the design and synthesis of diverse novel organic-inorganic hybrid nanomaterials, as well as fully utilizing traditional inorganic materials, provides the opportunity to enlarge the family of sensor devices. For example, Lu and Tai et al [2] designed and prepared the water-stable luminescent Zn II -metal organic framework (MOF) with the three-dimensional (3D) (2,3,8)-connected (4 3 ) 2 (4 6 .6 6 .8 15 .12)(8) topological framework, as characterized by single crystal X-ray diffraction based on H 2 PBA and 1,10-phenanthroline under solvothermal conditions. Interestingly [2], the following luminescence-sensing studies indicated that such hybrid architecture could be further developed as a multifunctional material for detecting metal cations such as Fe 3+ /Cu 2+ , pollutants such as trinitrophenol, as well as drugs such as colchicine, which may pave the way towards applying MOFs to chemical sensors.…”
mentioning
confidence: 99%